Protein Kinase A Gating of a Pseudopodial-located RhoA/ROCK/p38/NHE1 Signal Module Regulates Invasion in Breast Cancer Cell Lines - Cardone, Rosa A. (The American Society for Cell Biology, 2005)
Metastasis results from a sequence of selective events often involving interactions with elements of the tumor-specific physiological microenvironment. The low-serum component of this microenvironment confers increased motility and invasion in breast cancer cells by activating the Na(+)/H(+) exchanger isoform 1 (NHE1). The present study was undertaken to characterize the signal transduction mechanisms underlying this serum deprivation-dependent activation of both the NHE1 and the concomitant invasive characteristics such as leading edge pseudopodia development and penetration of matrigel in breast cancer cell lines representing different stages of metastatic progression. Using pharmacological and genetic manipulation together with transport and kinase activity assays, we observe that the activation of the NHE1 and subsequent invasion by serum deprivation in metastatic human breast cells is coordinated by a sequential RhoA/p160ROCK/p38MAPK signaling pathway gated by direct protein kinase A phosphorylation and inhibition of RhoA. Fluorescence resonance energy transfer imaging of RhoA activity and immunofluorescence analysis of phospho-RhoA and NHE1 show that serum deprivation dynamically remodels the cell, forming long, leading edge pseudopodia and that this signal module is preferentially compartmentalized in these leading edge pseudopodia, suggesting a tight topographic relation of the signaling module to an invasion-specific cell structure.